(untitled) (Jurnal Adabiya, 2017)
The emergence of a cult is a prominent issue in Aceh in the last decade. Some stream cults have highly attractiveness power, especially among young people and students, so that they are joining into this stream. This situation led to unrest in people’s daily lives, especially among the parent, religious leaders and community leaders. One way to reduce the appearance of this cult is through reinforcement the local wisdom. Based on local knowledge Aceh there are three forces that must be reaffirmed, namely, household, informal leaders in villages and educational institutions. Through the strengthening of the three institutions, it is hoped, a cult will not develop in Aceh